Beyond the Screen: Methods for Investigating Geographies of Life 'Online'. Issue 8 (2nd August 2013) - Kinsley, Samuel
Abstract: The internet and being 'online' is an integral part of everyday life for a substantial proportion of the population. There is an increasing impetus for researchers to engage with 'online' activities, not only as particular activities themselves but also as a part of the context of a wide range of geographies. The purpose of this article is to offer an overview of contemporary methodologies of researching geographies of life online. The article is structured in four sections. Beginning with a discussion of how to address a 'field', the article goes on to explore how geographers have addressed spatial understandings of the internet. Subsequently, themes of identity and authenticity are raised as key concerns for studies of life online, and accordingly the article moves on to discuss the ethics of such research. This article demonstrates how geographical thinking can inform and enhance social scientific research concerning the internet, particularly in relation to the articulation of spatial experience and knowledge.